The role of freshwater sludge and its carbonaceous derivatives in the removal of lead, phosphorus and antibiotic enrofloxacin: sorption characteristics and performance - Zhang, Yunhui (2022)
Freshwater sludge (FS) produced from drinking water treatment plants is generally filter pressed and disposed in the landfill. However, FS could be potentially reused. In this study, FS were processed into biochar and hydrochar via pyrolysis and hydrothermal carbonization, respectively. The sorption characteristics/mechanisms of FS and its derivatives (biochar-B300, B500 and B700 and hydrochar-H140, H160, H180 and H200) for the removal of three typical pollutants (i.e., lead (Pb), phosphorus (P) and enrofloxacin (ENR)) found in swine wastewater were investigated using batch adsorption tests and microstructural analyses. It was found that Pb sorption was relatively enhanced due to the increased electrostatic attraction and surface precipitation of Pb(OH)2 while the anionic phosphate adsorption relatively decreased as a result of enhanced electrostatic repulsion at higher solution pHs. Comparatively, ENR adsorption was less affected by solution pH probably due to dominance of physical adsorption evidenced by the good fitting of the BET isotherm model (R2 = 0.95). The maximum sorption capacities of Pb were in the order of B700≈B500 (71 mg/g)>B300 ~ FS(37 mg/g)>H140 ~ H160 (13 mg/g)>H180 ~ H200 (6 mg/g). The adsorption capacities for P were relatively lower: FS (47 mg/g)>B300 (38 mg/g)>H140 (27 mg/g)>B700 (37 mg/g)≈B500 (24 mg/g)≈H160 (23 mg/g)>H180 (16 mg/g)>H200 (14 mg/g). This study provides an understanding of the sorption characteristics and mechanisms of FS and its carbonaceous products for common cationic, anionic and organic pollutants and elucidates new insights into the reuse of FS for pollutant removal to achieve the waste-to-resource concept and enhance water quality, soil health and food safety.